The complete novels of Jane Austen. - Austen, Jane, 1775-1817 (New york : Race point publishing, 2012)
"Contains all six finished novels written by Jane Austen: Sense and Sensibility (1811), Pride and Prejudice (1813), Mansfield Park (1814), Emma (1815), Northanger Abbey (1818), and Persuasion (1818)"--
Sense and sensibility -- Pride and prejudice -- Mansfield Park -- Emma -- Northanger Abbey -- Persuasion.
AAL
Keywords: Romance fiction, English; England -- Social life and customs -- Fiction; Novels; Fiction